Cannulated Screw Fixation of Femoral Neck Fractures: An Intraoperative Pearl to Avoid a Common Mistake. Issue 4 (December 2021) - Paziuk, Taylor; Chang, Gerard; Krieg, James
Abstract : Percutaneous cannulated screw fixation is a well-described and relatively successful technique aimed at addressing femoral neck fractures. The advantages of this technique are limited primarily to its small surgical footprint and ability to preserve native femoral neck bone stock. Although the "3-point principle" described by Bout and colleagues aims at minimizing the potential complications and modes of mechanical failure of this fixation technique, the new literature suggests that our intraoperative radiographs may not be as reliable at detecting erroneous screw position as we may think. Hoffmann and colleagues recently demonstrated through a cadaveric study that 70% of the cranial-posterior screw in the "inverted triangle" construct, which were deemed cortically contained on fluoroscopy, actually breached the cortex. Although the clinical ramifications of this technical error are not fully understood, there is undoubtedly concern surrounding the biomechanical impact of altering the femoral neck's ability to resist tension while upright and compression while seated because of the location of this breach. This article aims to provide a technical pearl for accurately placing screws to abut the femoral neck cortex while avoiding cortical breach in the "inverted triangle" fixation construct.